Angka Kuman Udara Ruang Radiologi BP4 Yogyakarta Setelah Disinfeksi dengan Sinar Ultra Violet - Rusdiyanti Nurhanifah (Poltekkes Kemenkes Yogyakarta, 2010)
The human resources in BP4 Yogyakarta pose risk to acquire diseases es- pecially respiratory disease which are spread through the air. Based from the preliminary survey it is known that the number of air microorganism in the radi- ology exceeded the maximum limit regulated in Ministry of Health decree No. 1204/Menkes/SK/X/2004. One effort to control the microorganism is by conducting disinfection with ultraviolet. The disinfection should be regularly implemented in order to keep the number of air microorganisms below the treshold. The objectives of the research is to know the influence of ultraviolet disinfection toward the decline of air microorganism number and the required disinfection period. The method of the research is quasi-experiment following times series design. The location of the research is radiology room of BP4 Yogyakarta. The samples was taken before disinfection and after the 1st, 2nd, 3rd, 4th 5th and 6th day to measure the declining. The results show that disinfection with ultraviolet can reduce the number of air microorganisms in average of 86,1%, and this number has fulfilled the requirement. Based on the regression analysis, the num- ber of air microorganisms is predicted to reach the permitted treshold in the 3rd day after disinfection, therefore the disinfection should be conducted every 3 days.